Algorithmic game theory : 13th international symposium, SAGT 2020, Augsburg, Germany, September 16-18, 2020 Proceedings /: 13th international symposium, SAGT 2020, Augsburg, Germany, September 16-18, 2020 Proceedings. (2020) - Unknown
No abstract available